Eksperimen Pembelajaran Matematika Dengan Strategi Mind Mapping Dan Concept Maps Ditinjau Dari Kemampuan Berfikir Kreatif Matematis Pada Siswa Kelas VIII SMP Negeri 1 Kartasura Tahun Ajaran 2015/2016 - Indah Mariyana, Evit; , Dra. Nining Setyaningsih,M.Si (2016)
ABSTRACT Evit Indah Mariyana / A410120190. EKSPERIMEN PEMBELAJARAN MATEMATIKA DENGAN STRATEGI MIND MAPPING DAN CONCEPT MAPS DITINJAU DARI KEMAMPUAN BERFIKIR KREATIF MATEMATIS PADA SISWA KELAS VIII SMP NEGERI 1 KARTASURA TAHUN AJARAN 2015/2016. Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Surakarta, Juni 2016 The purpose of this study to examine (1) the effect of the strategy Mind Mapping and Concept Maps towards mathematics learning achievement of students, (2) the effect of level of ability to think creatively mathematical towards mathematics learning achievement of students, (3) the interaction between the learning strategies and the ability to think creatively mathematically towards mathematics learning achievement of students. Quantitative research with a quasi-experimental design. Population and sample Junior High School eighth grade students Kartasura. The sampling technique using cluster random sampling. The data collection technique using the test methods, questionnaire and documentation. Data were analyzed using analysis of variance of two paths with different cell. The results of the study with α = 5% is (1) There is a significant relationship bet strategy use Mind Mapping and Concept Maps to the mathematics learning achievement of students, (2) There is significant influence mathematics learning achievement of students in terms of the ability of creative thinking mathematically, (3) there is no interaction between the learning strategies and the ability to think creatively mathematical mathematics learningachievement of students. Keywords: Mind Mapping, Concept Maps, Creative mathematical, mathematics achievement of students.